2013
DOI: 10.1007/s00221-013-3720-0
|View full text |Cite
|
Sign up to set email alerts
|

Coordination deficits during trunk-assisted reach-to-grasp movements in Parkinson’s disease

Abstract: The present study investigated how Parkinson’s disease (PD) affects temporal coordination among the trunk, arm, and fingers during trunk-assisted reach-to-grasp movements. Seated participants with PD and healthy controls made prehensile movements. During the reach to the object, the involvement of the trunk was altered based on the instruction; the trunk was not involved, moved forward (flexion), or moved backward (extension) in the sagittal plane. Each of the trunk movements was combined with an extension or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 73 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…In particular, the magnitudes of the variability measures were significantly correlated with the severity of PD in reach-to-grasp movements (Alberts et al 2000; Rand et al 2014). Our earlier studies have shown that changes in the magnitude of variability in PD are associated with significant changes in the structure of variance during a relatively artificial, constrained pressing task (Park et al 2012, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the magnitudes of the variability measures were significantly correlated with the severity of PD in reach-to-grasp movements (Alberts et al 2000; Rand et al 2014). Our earlier studies have shown that changes in the magnitude of variability in PD are associated with significant changes in the structure of variance during a relatively artificial, constrained pressing task (Park et al 2012, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Trunk control is important in terms of neurorehabilitation which is used for stroke and other movement disorders (Parkinson etc.) [7][8][9][10] . Based on this knowledge, evaluation of early trunk control, mobility and functional independence in patients with brain tumors after surgery is so important in our clinical practice.…”
Section: Introductionmentioning
confidence: 99%